Nel·lo, Oriol (2015). La ciudad en movimiento: Crisis social y respuesta ciudadana - Donat Muñoz, Carles (Documents d’Anàlisi Geogràfica, 2017)
Nel·lo, Oriol (2015) La ciudad en movimiento: Crisis social y respuesta ciudadana Madrid: Díaz & Pons, 205 p. ISBN 978-84-944522-0-8